Wall slipping behavior of foam with nanoparticle-armored bubbles and its flow resistance factor in cracks - Qichao Lv (Nature Portfolio, 2017)
Abstract In this work, wall slipping behavior of foam with nanoparticle-armored bubbles was first studied in a capillary tube and the novel multiphase foam was characterized by a slipping law. A crack model with a cuboid geometry was then used to compare with the foam slipping results from the capillary tube and also to evaluate the flow resistance factor of the foam. The results showed that the slipping friction force F FR in the capillary tube significantly increased by addition of modified SiO2 nanoparticles, and an appropriate power law exponents by fitting F FR vs. Capillary number, Ca, was 1/2. The modified nanoparticles at the surface were bridged together and formed a dense particle “armor” surrounding the bubble, and the interconnected structures of the “armor” with strong steric integrity made the surface solid-like, which was in agreement with the slip regime associated with rigid surface. Moreover, as confirmed by 3D microscopy, the roughness of the bubble surface increased with nanoparticle concentration, which in turn increased the slipping friction force. Compared with pure SDBS foam, SDBS/SiO2 foam shows excellent stability and high flow resistance in visual crack. The resistance factor of SiO2/SDBS foam increased as the wall surface roughness increased in core cracks.